2008
DOI: 10.1016/j.jtcvs.2007.07.073
|View full text |Cite
|
Sign up to set email alerts
|

Remediastinoscopy in restaging of lung cancer after induction therapy

Abstract: Remediastinoscopy provides a histologic proof of mediastinal downstaging with high diagnostic accuracy, is technically feasible with low morbidity, and still remains a valuable tool, even in an era of highly sophisticated imaging and endoscopic procedures. Persisting nodal disease at repeat mediastinoscopy carries a poor survival in the majority of cases because of occult metastases, so that indication for surgical intervention in such an unfavorable group of patients should be evaluated very carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 26 publications
3
36
0
5
Order By: Relevance
“…Because we performed diagnostic tests in a high-prevalence setting of recurrent NSCLC, the increased prevalence resulted in a decreased NPV. However, the NPV was still comparable with previously reported NPVs for remediastinoscopy of 73.3-84.5% (26)(27)(28).…”
Section: Discussionsupporting
confidence: 87%
“…Because we performed diagnostic tests in a high-prevalence setting of recurrent NSCLC, the increased prevalence resulted in a decreased NPV. However, the NPV was still comparable with previously reported NPVs for remediastinoscopy of 73.3-84.5% (26)(27)(28).…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that Med is also able to provide a prognostic information. Other studies reported similar performance characteristics for Med with sensitivity of 61-83%, diagnostic accuracy of 84-91% and NPV of 85% (96)(97)(98)100). One, study however, showed very low sensitivity and diagnostic accuracy of Med, 29% and 60%, respectively, which was presumed to be due to inadequate sampling of station 7 LN in majority of patients (99).…”
Section: Ebus-tbna and Med-role In Lung Cancer Diagnosismentioning
confidence: 78%
“…Both Med and EBUS-TBNA have been used for mediastinal restaging (41,(96)(97)(98)(99)(100)(101)(102). However, performance of both Med and EBUS-TBNA in restaging is worse than in original staging.…”
Section: Ebus-tbna and Med-role In Lung Cancer Diagnosismentioning
confidence: 99%
“…The number of removed or biopsied lymph nodes varied in the published series, but was significantly higher, than in the endoscopic needle aspiration techniques. Persisting nodal disease at repeat mediastinoscopy carries a poor survival in the majority of cases because of occult metastases; therefore, indication for surgical intervention in such an unfavourable group of patients should be evaluated very carefully [80,[87][88][89][90].…”
Section: Diagnosis For Mediastinal Nodes (N-status)mentioning
confidence: 99%